NBR1 enables autophagy-dependent focal adhesion turnover - Kenific, Candia M. (J Cell Biol, 2016)
Autophagy is a catabolic pathway involving the sequestration of cellular contents into a double-membrane vesicle, the autophagosome. Although recent studies have demonstrated that autophagy supports cell migration, the underlying mechanisms remain unknown. Using live-cell imaging, we uncover that autophagy promotes optimal migratory rate and facilitates the dynamic assembly and disassembly of cell-matrix focal adhesions (FAs), which is essential for efficient motility. Additionally, our studies reveal that autophagosomes associate with FAs primarily during disassembly, suggesting autophagy locally facilitates the destabilization of cell-matrix contact sites. Furthermore, we identify the selective autophagy cargo receptor neighbor of BRCA1 (NBR1) as a key mediator of autophagy-dependent FA remodeling. NBR1 depletion impairs FA turnover and decreases targeting of autophagosomes to FAs, whereas ectopic expression of autophagy-competent, but not autophagy-defective, NBR1 enhances FA disassembly and reduces FA lifetime during migration. Our findings provide mechanistic insight into how autophagy promotes migration by revealing a requirement for NBR1-mediated selective autophagy in enabling FA disassembly in motile cells.